Features of the Management of Patients with Long-Term Forms of Chronic Sinusitis - Khamrakulova Nargiza Orzuyevna (Genius Journals, 2023)
The main objective of functional microendoscopic surgery of the sinuses is to restore the area of the medullary complex and restore air exchange and drainage function of the altered sinuses through physiological pathways. Removal of purulent and polyposis tissue from the cells and walls expanded from polyposis tissue was carried out under the control of the endoscope.
Keywords: purulent sinusitis; polyposic maxillary sinusitis; microendosurgery